Photobiomodulation Can Enhance Stem Cell Viability in Cochlea with Auditory Neuropathy but Does Not Restore Hearing - So-Young Chang; Eunjeong Kim; Nathaniel T. Carpena; Jae-Hun Lee; Doo Hee Kim; Min Young Lee (Stem Cells International)
Sensorineural hearing loss is very difficult to treat. Currently, one of the techniques used for hearing rehabilitation is a cochlear implant that can transform sound into electrical signals instead of inner ear hair cells. However, the prognosis remains very poor if sufficient auditory nerve cells are not secured. In this study, the effect of mouse embryonic stem cells (mESC) and photobiomodulation (PBM) combined treatment on auditory function and auditory nerve cells in a secondary neuropathy animal model was investigated. To confirm the engraftment of stem cells in vitro, cochlear explants were treated with kanamycin (KM) to mimic nerve damage and then cocultured with GFP-mESC. GFP-mESCs were observed to have attached and integrated into the explanted samples. An animal model for secondary neurodegeneration was achieved by KM treatment and was treated by a combination therapy of GFP-mESC and NIR-PBM at 8 weeks of KM treatment. Hearing recovery by functional testing using auditory brain stem response (ABR) and eABR was measured as well as morphological changes and epifluorescence analysis were conducted after 2 weeks of combination therapy. KM treatment elevated the hearing threshold at 70–80 dB and even after the combination treatment with GFP-mESC and PBM was applied, the auditory function was not restored. In addition, the stem cells transplanted into cochlea has exponentially increased due to PBM treatment although did not produce any malignancy. This study confirmed that the combined treatment with mESC and PBM could not improve hearing or increase the response of the auditory nerve. Nevertheless, it is noteworthy in this study that the cells are distributed in most cochlear tissues and the proliferation of stem cells was very active in animals irradiated with PBM compared to other groups wherein the stem cells had disappeared immediately after transplantation or existed for only a short period of time.